Distributed single mode fiber sensor and fiber Bragg grating for displacement and temperature sensing / Nor Jannah Muhamad Satar - Muhamad Satar, Nor Jannah (2012)
This dissertation discuss the research works on distributed optical fiber sensor system consisting of optical fiber-loop sensor incorporating fiber Bragg grating (FBG) for displacement and temperature detections. The fiber-loop sensor was designed using single mode fiber (SMF) to exhibit signal attenuation due to the macrobending perturbation in the optical fiber. A novel fiber-loop design was used to investigate the optical attenuation due to macrobending effect in the fiber-loop. The bending effect would cause higher optical signal loss when the fiber-loop diameter is further reduced due to the force action of displacement The single mode fiber sensor (SMF-sensor) was characterized using optical time domain reflectometer (OTDR), optical spectrum analyzer (OSA), and optical power meter (0PM and OFM). Single SMF-sensor was characterized and the result was used in developing a distributed sensing system consists of three SMF-sensors along the monitoring line. The SMF-sensor is capable to detect faults simultaneously at several different locations. The fiber-loop sensing head has a sensitivity of 0.044 dB/mm and 0.024 dB/mm measured using OTDR and OSA respectively. OTDR provides higher sensitivity in detecting displacement per millimetre unit besides precisely locate the fault point. The SMF-sensor was installed on lab—scale hill-slope simulator to test the response of the optical signal when the slope structure was displaced at different directions. SMF- sensor gives higher responsive when detecting displacement in horizontal-direction with a recorded sensitivity of 0.175 dB/mm and able to detect ground displacement initially at 5±0.1mm displacement. FBG incorporated m the system served as temperature sensor. FBG recorded a sensitivity of 0.01 nm/°C when detected temperature changes.